Analysis of determinants in physical education achievement: Nutritional knowledge and body mass index - Deby Tri Mario; Zikri Muthahari; Pramudya Wisnu Priambodo; Iqbal Maulana; Yovhandra Ockta; Idarul Hafni; Rahman Rahman; Iken Rahma Mahesty; Salma Alfina Putri Nada (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2026)
This study aims to analyze the effect of Nutrition Knowledge (NK) and Body Mass Index (BMI) on Physical Education (PE) learning outcomes in elementary school students, both partially and simultaneously. This study used an associative quantitative approach involving 28 third-grade students aged between 8-9 years. NK was measured using a multiple-choice questionnaire, BMI was obtained through anthropometric measurements, while PE learning outcomes were obtained from students' report card scores. The data were analyzed using simple and multiple linear correlation and regression. The results showed that the students' NK was in the adequate category (M=70.107±0.875), BMI was in the normal category (M=-1.626±0.977), and PE learning outcomes were in the adequate category (M=77.679±4.514). Regression analysis showed that NK and BMI had a positive and significant effect on PE learning outcomes, with BMI having a greater effect than NK (partially, R²=0.360; R²=0.472; p=0.001; and simultaneously, R²=0.656; p=0.001). These findings indicate that good NK and normal BMI contribute to improved PE learning outcomes in elementary school students. Further research is recommended using a longitudinal design with a larger sample size and considering relevant behavioral and environmental factors to obtain a more comprehensive understanding of the factors that influence PE learning outcomes.